Categorical perception of color decreases in individuals with methamphetamine use disorder. (February 2021) - Li, Ping; Zhang, Mingming; Zhu, Chuanlin; Leng, Yexi; Li, Yuchen; He, Weiqi; Luo, Wenbo
Highlights: Categorical color perception attenuates in methamphetamine use disorders. More depression and lower sleep quality in methamphetamine use disorders than controls. Categorical color perception is irrelevant to methamphetamine use history.